1987
DOI: 10.1136/jcp.40.4.412
|View full text |Cite
|
Sign up to set email alerts
|

Xanthogranulomatous cholecystitis: clinicopathological study of 13 cases.

Abstract: SUMMARY In a retrospective three year study 13 cases of xanthogranulomatous cholecystitis (XGC) (seven female, six male) were found in 724 gallbladders (1 8%), an estimated incidence of 1 7 cases per 1O00000 population per annum. Symptoms often began with an episode of acute cholecystitis and persisted for up to five years. There was extension of xanthogranulomatous tissue into adjacent organs in nine cases. Three patients had fistulae from the gall bladder, one to skin, and two to the duodenum; this is the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
117
0
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(123 citation statements)
references
References 6 publications
5
117
0
1
Order By: Relevance
“…Previous studies have shown that gallbladder cancer occurs alongside XGC in 2 to 35.4% of cases. 4 In the present study, XGC was not associated with gallbladder carcinoma in any of the patients. A preoperative diagnosis of XGC is difficult, and intraoperative diagnosis from a frozen section is often needed to differentiate XGC from carcinoma.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Previous studies have shown that gallbladder cancer occurs alongside XGC in 2 to 35.4% of cases. 4 In the present study, XGC was not associated with gallbladder carcinoma in any of the patients. A preoperative diagnosis of XGC is difficult, and intraoperative diagnosis from a frozen section is often needed to differentiate XGC from carcinoma.…”
Section: Discussionmentioning
confidence: 55%
“…The XGC regions present themselves as yellow masses within the wall of the gallbladder when examined macroscopically. 4 The pathogenesis of XGC is unclear, but the extravasated bile conceivably originating from ruptured Rokitansky-Aschoff sinuses is purported to be the cause of this inflammatory response. 4,5 Concomitant cholelithiasis is observed in most XGC cases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[5,6] Clinical examination may not be helpful to distinctly diagnose xanthogranulomatous cholecystitis, though a history of similar episodes in the past can be elicited thus making it difficult to differentiate from other inflammatory gall bladder diseases and cholelithiasis. [3,7] Ultrasonogram of the abdomen and CT reveal only gallbladder thickening and presence of gallstones, which are congruous to any form of cholecystitis -thus making the preoperative diagnosis obscure. [6,7] B-mode ultrasound can sometimes help in diagnosis of xanthogranulomatous cholecystitis if the features like hypoechoic intraluminal nodules with hyperechoic thickened gallbladder wall are seen, but these often get missed owing to rarity in incidence and scarcity of knowledge about this disease, thus warranting the need to confirm the diagnosis on histopathological grounds.…”
Section: Discussionmentioning
confidence: 99%
“…[3,7] Ultrasonogram of the abdomen and CT reveal only gallbladder thickening and presence of gallstones, which are congruous to any form of cholecystitis -thus making the preoperative diagnosis obscure. [6,7] B-mode ultrasound can sometimes help in diagnosis of xanthogranulomatous cholecystitis if the features like hypoechoic intraluminal nodules with hyperechoic thickened gallbladder wall are seen, but these often get missed owing to rarity in incidence and scarcity of knowledge about this disease, thus warranting the need to confirm the diagnosis on histopathological grounds. [5,6] MRCP and ERCP can not only diagnose the anatomy of the biliary tree, but also relieve the obstruction and obtain biopsy.…”
Section: Discussionmentioning
confidence: 99%